2016
DOI: 10.1007/s00296-016-3552-x
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal injury in NSAID users suffering from rheumatoid arthritis or osteoarthritis

Abstract: The goal of this prospective study was to assess non-steroidal anti-inflammatory drug (NSAID)-induced enteropathy in patients with rheumatoid arthritis (RA) or osteoarthritis (OA) by means of non-invasive wireless capsule enteroscopy. A total of 143 patients (74 with RA, 69 with OA) treated with NSAIDs (>1 month) and 42 healthy volunteers were included. All subjects underwent capsule endoscopy, laboratory tests and filled in questionnaires. The severity of small bowel injury was graded as: mild (red spots or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
10
1
3
Order By: Relevance
“…The cause of ulcerative small intestinal lesions may be NSAIDs, anticoagulants including low-dose aspirin, or an increase in infectious small intestinal disease. 11,12 NSAIDs damage the small intestinal mucosa at a high rate, 13 but no significant difference was noted in our findings.…”
Section: Discussioncontrasting
confidence: 61%
“…The cause of ulcerative small intestinal lesions may be NSAIDs, anticoagulants including low-dose aspirin, or an increase in infectious small intestinal disease. 11,12 NSAIDs damage the small intestinal mucosa at a high rate, 13 but no significant difference was noted in our findings.…”
Section: Discussioncontrasting
confidence: 61%
“…Reports have shown that approximately 1% of the world population is suffering from RA and that OA affects mainly the elderly 2,3. Nonsteroidal anti-inflammatory drugs (NSAIDs) have been reported to be widely used in RA and OA therapy 4,5. However, NSAIDs can induce renal and gastrointestinal toxicities because they inhibit prostaglandin synthesis, thus limiting the clinical application of NSAIDs 6.…”
Section: Introductionmentioning
confidence: 99%
“…The lesions were mostly mild (36.4%), less frequently moderate (3.5%), or severe (4.9%). 22 VCE showed a high (~70%) rate of small bowel abnormality in chronic NSAID users (> 3 months); 50% patients had mild and 25% of the patients. 23 While VCE is highly sensitive for mucosal lesions, the relevance of these findings is difficult to establish.…”
Section: Endoscopic Studiesmentioning
confidence: 95%